ASCARIDOLE AND RELATED PEROXIDES FROM THE GENUS CHENOPODIUM - Dembitsky, Valery; Shkrob, Ilya; Hanus, Lumir Ondrej (Biomedical papers, 2008)
AIM: Detection of monoterpenoid ascaridole and other terpenoids in the genus Chenopodium from the East Mediterranean.METHOD: Distribution of ascaridole in leaves of 13 species medicinal plant belonging to the genus Chenopodium was examined with the help of the GC MS method.RESULTS: cis Ascaridole was found as a major peroxy monoterpenoid (up to 46.9 %) in the oil. Three minor isomers: cis isoascaridole (1.1 6.4 %), trans ascaridole (1 2 %), and trans isoascaridole (1 2 %) were also detected. The biological activities and biosynthesis of ascaridole are further discussed.CONCLUSIONS: The results on Ascaridol and the major volatiles and semi volatiles of wild species belonging to the genus Chenopodium provide important information on biologically active monoterpenoid compounds and volatile metabolites biosynthesized in wild medicinal plants growing in the East Mediterranean.
Keywords: Chenopodium/Ascaridole/Terpenoids/Medicinal plant/Peroxides